Sémantický popis multimediálních souborů pomocí sociálních sítí - Michálek, Karel (Univerzita Pardubice, 2007)
This article deals with making intonations of using a social network to describe multimedia objects as another way of semantic description of non-text information. An environment for social network was using FOAF standards. This paper suggests methods of social network analysis for semantic description of multimedia objects. These methods are an interesting supplement of current methods.
Keywords: SNA; sociální sítě; Multimedia; sémantický popis; FOAF